Stanisław Moniuszko and Apolinary Kątski: the Slander and the Facts - Chamczyk, Ewa (Interdisciplinary Studies in Musicology, 2025)
This article examines the complex and dynamic relationship between two prominent 19th-century Polish musicians: composer Stanisław Moniuszko (1819–1872) and violinist Apolinary Kątski (1824–1879). Drawing on extensive correspondence and contemporary accounts, the study traces the evolution of their interactions from initial antipathy to ostensible reconciliation and subsequent professional collaboration. The research focuses on key events that shaped their relationship, including their first encounter, public debates over musical aesthetics, and their work together at the Warsaw Institute of Music. Particular attention is given to the controversial circumstances surrounding Moniuszko’s death and subsequent accusations against Kątski. By critically analyzing primary sources, the article challenges some long-held assumptions about their relationship and offers a more nuanced understanding of the personal and professional tensions between these two influential figures in 19th-century Polish musical life. This study contributes to a broader understanding of the social and cultural dynamics within Poland’s musical circles during this period and provides new insights into the careers and legacies of both Moniuszko and Kątski.